2007
DOI: 10.1080/01612840701581255
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Tai Chi, Yoga, Meditation, and Reiki Healing Sessions in Promoting Health and Enhancing Problem Solving Abilities of Registered Nurses

Abstract: Given the current necessity of retaining qualified nurses, a self-care program consisting of Yoga, Tai Chi, Meditation classes, and Reiki healing sessions was designed for a university-based hospital. The effectiveness of these interventions was evaluated using self-care journals and analyzed using a Heideggerian phenomenological approach. Outcomes of the self-care classes described by nurses included: (a) noticing sensations of warmth, tingling, and pulsation which were relaxing, (b) becoming aware of an enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 20 publications
(20 reference statements)
6
46
0
5
Order By: Relevance
“…Even participants who have never practised taiji felt the essence of 'qi' during the experiential session: Feels like something between the palms…cannot easily push palms together. Participant C The themes emerging within the group discussions echo those in the published literature: improved sleep (Caldwell et al 2009); improved mobility and balance (Li et al 2001); and elements of positive well being and creativity explicated through the poem which illustrated the joy of the sensations and movements whilst performing taiji (Sandland and Norlander 2000;Raingruber and Robinson 2007). A sense of calmness and relaxation is in keeping with the findings of Taylor -Piliae et al (2006), Raingruber and Robinson (2007) and Baron and Faubert (2005).…”
Section: Feedback From Group Discussion At the Workhopsupporting
confidence: 60%
See 2 more Smart Citations
“…Even participants who have never practised taiji felt the essence of 'qi' during the experiential session: Feels like something between the palms…cannot easily push palms together. Participant C The themes emerging within the group discussions echo those in the published literature: improved sleep (Caldwell et al 2009); improved mobility and balance (Li et al 2001); and elements of positive well being and creativity explicated through the poem which illustrated the joy of the sensations and movements whilst performing taiji (Sandland and Norlander 2000;Raingruber and Robinson 2007). A sense of calmness and relaxation is in keeping with the findings of Taylor -Piliae et al (2006), Raingruber and Robinson (2007) and Baron and Faubert (2005).…”
Section: Feedback From Group Discussion At the Workhopsupporting
confidence: 60%
“…It was also felt that the calmness they experienced provided them with the ability to better pick up on cues from patients. The nurses participating in the study also reported having a more positive view of their work (Raingruber and Robinson 2007).…”
Section: Reviewing the Literaturementioning
confidence: 85%
See 1 more Smart Citation
“…Nötral şeyler, olaylar, insanlar bilinç dışına atılmaktadır, genellikle dikkat vermeye değer bulunmamaktadır (Kabat-Zinn 2009). Bu kategorizasyon ve yargılama alışkanlığının çoğu zaman farkında dahi olunmamakta, kişi mekanik reaksiyonlar gös-termektedir (Raingruber 2007). Bu yargılamalar zihinleri yönetme eğilimindedir ve insanların kendi içinde huzur bulmasının önünde büyük bir engeldir (Matchim ve ark.…”
Section: Yargılamamaunclassified
“…Raingruber (2007) kişinin kendi sezgilerine ve uzmanlı-ğına güvenmesinin, bazen hata yapsa bile, attığı adımları, yaşamını ve kararlarını dışarı-dakilerin yönlendirmesinden çok daha iyi olduğunu belirtmektedir. Kendine, kendi bilgeliğine ve erdemine güvenme tutumu meditasyon uygulamasının önemli bir unsurudur (Tsang ve ark.…”
Section: Güvenunclassified